Antiretroviral combination use during pregnancy and the risk of major congenital malformations. (23rd October 2017) - Bérard, Anick; Sheehy, Odile; Zhao, Jin-Ping; Abrahamowicz, Michal; Loutfy, Mona; Boucoiran, Isabelle; Bernatsky, Sasha
Abstract : Objective: To quantify the risk of major congenital malformations (MCMs) associated with gestational combination antiretroviral use. Design: Population-based prospective cohort study. Methods: Using the Quebec Pregnancy Cohort from 1998 to 2015, we included women who were covered by the Quebec Drug Plan and had a singleton livebirth. All antiretroviral use alone or in combination were considered. MCMs overall and organ-specific malformations in the first year of life were identified. Results: In total, 214 240 pregnancies met inclusion criteria; 0.09% ( n  = 198) occurred while on antiretroviral combinations during the first trimester; 169 HIV-positive women without antiretroviral treatment were included. Compared with the general population in this cohort, the prevalence of MCMs was significantly higher in unexposed HIV-positive women (14.8 vs. 8.6%, P  = 0.004) but not in antiretroviral-exposed HIV-positive women (10.3%, P  = 0.41). Adjusting for potential confounders, including maternal HIV status, antiretroviral use during the first trimester was not associated with the risk of MCMs (adjusted odds ratio 0.59, 95% confidence interval 0.33–1.06). However, antiretroviral combination use during the first trimester was associated with an increased risk of defects of the small intestine (adjusted odds ratio 10.32, 95% confidence interval 2.85–37.38, P  = 0.0004). Conclusion: Antiretroviral therapy during the first trimester was not associated with the risk of overall MCMs but may be associated with an increased risk of defects of the small intestine. However, HIV-positive pregnant women who are not treated with antiretrovirals during pregnancy seem to have a higher risk of malformations; this is not seen among those who are treated, which could indicate that the underlying condition puts women at risk and not the treatment. Abstract : Supplemental Digital Content is available in the text